Goal Orientations and the Motivation to Share Knowledge - Swift,Michele; Balkin,David B.; Matusik,Sharon (Journal of Knowledge Management, 2010)
Drawing from research on achievement motivation and social exchange, a model is developed highlighting how goal orientations provide a framework for individuals’ knowledge sharing by shaping how they cognitively value the costs and benefits associated with sharing their knowledge. We argue each of the goal orientations are associated with preferences for sharing specific types of knowledge and a focus on different aspects of the knowledge provider-recipient relationship.
Keywords: Management

Understanding when Knowledge Sharing Benefits Knowledge Sources' Creativity - Swift,Michele; Matusik,Sharon; George,Jennifer (Annual Meeting of the Academy of Management, 2009)
Keywords: Management